Training for Making Local Woven Motifs with Textile Painting - Salniwati, Salniwati; Nurtikawati, Nurtikawati (Journal of Community Service and Society Empowerment, 2025)
The community service activity entitled, "Training in making local woven motifs based on textile painting techniques" was held on May, 2025. This activity was the result of a collaboration between the community service team and the Pondok Suraya Creative Center Studio which focuses on developing artistic creativity based on local culture. The main objective of this activity was to increase the knowledge and skills of studio members in understanding and applying the richness of typical Southeast Sulawesi woven motifs into alternative media, namely textile painting. The method used was community education through presentation of community service and training materials. This activity demonstrates the participants' ability to re-explain the meaning and types of Southeast Sulawesi woven motifs, as well as the accuracy in applying motifs to textile paintings. This achievement is seen as important as part of cultural preservation as well as a strategy for empowering creative communities.